Analisis Spasial Pengelolaan Sampah Rumah Tangga di Kota Bukittinggi - Zuhdi, Iqbal; Syarief, Azhari (Lembaga Yasin AlSys, 2024)
This study aims to determine the distribution pattern of landfills in the city of Bukittinggi and the route of waste transportation vehicles so that people know the time and route of waste disposal. This research uses a quantitative method used to calculate the value of the distribution of landfill areas in the city of Bukittinggi. The analysis technique used is to use nearest neighbor analysis with routes and tracking. After obtaining the route, data processing will be carried out using the ArcGis application so that a map of the garbage transportation distribution path is obtained. Based on the research that has been done, it is found that the distribution pattern of Bukittinggi TPS through Average Nearest Neighbor analysis using ArcMap application. 10.4.1 is random and more located close to the city center.